AKULTURASI AJARAN ISLAM DAN ADAT KARO DALAM TRADISI KELAHIRAN DI DESA TANJUNG ANOM KECAMATAN PANCUR BATU - Arifinsyah Arifinsyah; Indah Puspita Nasution (Studia Sosia Religia, 2022)
The main problem of this research, discusses "Acculturation of Islamic Teachings and Karo Customs in Birth Tradition in Tanjung Anom Village, Pancur Batu District". As for the main problem, the research is divided into two sub-problems, namely: 1) How is the ceremony of carrying out the Karo traditional birth, 2) How is the comparison of acculturation of Islamic teachings to the traditional Karo birth ceremony.This type of research is qualitative, with an anthropological approach. The source of the research data. First, primary data is data obtained by in-depth interviews with resource persons related to the object under study in this case such as traditional leaders, Muslim and non-Muslim communities, as well as several other community leaders, and documentation from the community in Tanjung Anom village. Second, secondary data is data whose sources are obtained from several books, journals, magazines, newspapers or online news, as well as other information related to the problem of acculturating Islamic teachings to the Karo birth custom of Tanjung Anom village.The result of this study is the acculturation of Islamic teachings in the Karo Adat Birth Tradition, that acculturation is a social process that arises when a group of people with a certain culture are confronted with elements of a foreign culture in such a way that the elements of foreign culture are gradually accepted and processed into their own culture without causing the loss of the culture itself. Meanwhile, Islamic teachings in welcoming births are different from Karo traditional traditions. Comparison of the acculturation of Islamic teachings to the traditional Karo birth ceremony, namely Islamic teachings following the Sunnah of the Prophet Muhammad SAW, of course it is very good if practiced for Muslims while the Karo custom birth tradition follows the teachings of previous ancestors.